Management of complex ischial-urethral fistula in neurogenic patients performing clean intermittent self-catheterization. Issue 1 (February 2023) - Ammirati, Enrico; Geretto, Paolo; Giammò, Alessandro; Falcone, Marco; Gontero, Paolo; Manassero, Alberto
Introduction: Neurogenic patients performing clean-intermittent self-catheterization (CIC) may develop an urethral erosion, resulting in ischial-urethral fistulas (I-UF). In this work we present our single-center experience in dealing with this peculiar complication. Methods: In this work we included all neurogenic patients performing CIC treated at out Institution for I-UF. All patients had a spinal cord injury or myelomeningocele. We extracted from the patients' medical records the surgical management and postoperative clinical data. We defined failure the persistence of the fistula at X-ray contrast fistulography, retrograde urethrography, or uretrocystoscopy. Results: We treated 11 patients (8 spinal cord injury, 3 myelomeningocele). Four patients have been treated with the placement of a new generation urethral stent (Uventa) after surgical toilette of the skin ulcer and placement of a temporary suprapubic catheter. All patients demonstrated a complete healing of the urethral lesion at stent removal and continued CIC without any difficulty. Four patients have been treated with perineal urethroplasty, requiring a buccal mucosal graft in two cases. In two patients a suprapubic permanent catheter was placed for a simpler bladder management due to the patients' comorbidities. In one case the incidental finding of an high grade muscle invasive urothelial bladder cancer, made it mandatory to perform an uretheroileocutaneostomy. Conclusions: This work represent a unique series of I-UF in neurogenic patients performing CIC. Surgical urethral reconstruction, often with the use of buccal mucosa in large lesions, may be a difficult solution in neurogenic patients, new generation stents (Uventa) represent a minimally invasive, effective, and safe alternative.